1997
DOI: 10.1073/pnas.94.22.12151
|View full text |Cite
|
Sign up to set email alerts
|

Operative GABAergic inhibition in hippocampal CA1 pyramidal neurons in experimental epilepsy

Abstract: Patch-clamp recordings of CA1 interneurons and pyramidal cells were performed in hippocampal slices from kainate-or pilocarpine-treated rat models of temporal lobe epilepsy. We report that ␥-aminobutyric acid (GABA)ergic inhibition in pyramidal neurons is still functional in temporal lobe epilepsy because: (i) the frequency of spontaneous GABAergic currents is similar to that of control and (ii) focal electrical stimulation of interneurons evokes a hyperpolarization that prevents the generation of action poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 30 publications
7
77
0
1
Order By: Relevance
“…For instance, robust periods of firing depression (presumably corresponding to IPSPs) have been recorded in electrophysiological studies performed presurgically with intracranial electrodes or extracellular unit recordings in TLE patients (Wilson and Engel, 1993;Isokawa-Akesson et al, 1989). Moreover, histochemical studies have demonstrated that some interneuron subtypes are preserved in both human and experimental animal epileptic tissue Davenport et al, 1990;Esclapez et al, 1997) even though some other subtypes are clearly decreased in number in specific limbic structures (de Guzman et al, 2006(de Guzman et al, , 2008.…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, robust periods of firing depression (presumably corresponding to IPSPs) have been recorded in electrophysiological studies performed presurgically with intracranial electrodes or extracellular unit recordings in TLE patients (Wilson and Engel, 1993;Isokawa-Akesson et al, 1989). Moreover, histochemical studies have demonstrated that some interneuron subtypes are preserved in both human and experimental animal epileptic tissue Davenport et al, 1990;Esclapez et al, 1997) even though some other subtypes are clearly decreased in number in specific limbic structures (de Guzman et al, 2006(de Guzman et al, , 2008.…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 99%
“…Later studies, however, have challenged this assumption, by showing that inhibition per se or some types of inhibitory mechanisms are preserved in animal models of epilepsy (Davenport et al, 1990;Esclapez et al, 1997;Prince & Jacobs, 1998;Cossart et al, 2001Cossart et al, , 2005 and in post-surgical human temporal lobe tissue (Isokawa-Akesson et al, 1989;Babb et al, 1989;Avoli and Olivier, 1989;Avoli et al, 1995;Cohen et al, 2002). Moreover, more complex, at times ambiguous, roles for GABAergic signaling in epilepsy were identified.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, inhibitory processes have been observed during different types of seizure activity (Esclapez et al 1997;Prince and Jacobs 1998;Prince et al 1997;Timofeev et al 2002b;Traub et al 1996). Recordings from human and rat slices (Cohen et al 2002;FujiwaraTsukamoto et al 2003) as well in vivo experiments in cats (Timofeev et al 2002b) have demonstrated that PDSs contain an important inhibitory component.…”
Section: Cellular Mechanisms Mediating Spike and Wave Dischargesmentioning
confidence: 99%
“…Accordingly, the traditional point of view is that the key intracellular correlate of epileptiform activity, the paroxysmal depolarizing shift (PDS), consists of a giant EPSP (Johnston and Brown 1981) enhanced by activation of voltageregulated intrinsic currents (de Curtis et al 1999;Dichter and Ayala 1987;Prince and Connors 1984;Westbrook and Lothman 1983;Wong and Prince 1978). It was therefore a surprise when more recent evidence showed that synaptic inhibition remains functional in many forms of paroxysmal activities (Cohen et al 2002;Davenport et al 1990;Engel et al 2003;Esclapez et al 1997;Higashima 1988;Prince and Jacobs 1998;Timofeev et al 2002b;Topolnik et al 2003;Traub et al 1996). Also, disruption of inhibitory function does not affect neocortical kindling (Denslow et al 2001), which is associated with an increases in synaptic strength that mediates recruitment of larger cortical areas (Teskey et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, in vitro analyses of hippocampi removed from post-SE epileptic animals, which exhibit widespread brain damage and seizures of undetermined origin (Bertram, 1997;Bertram et al, 2001;Harvey and Sloviter, 2005), may tend to underemphasize the epileptogenic contribution of the unexamined extrahippocampal structures, and to overemphasize the importance of the hippocampus by assuming, but not demonstrating, that the hippocampi of epileptic animals are "epileptic" (Tauck and Nadler, 1985;Wuarin and Dudek, 1996;Esclapez et al, 1997;Cossart et al, 2001;Bernard et al, 2004).…”
Section: Possible Functional Implicationsmentioning
confidence: 99%